(untitled) (Journal of Misan Researches, 2021)
The research seeks to show the impact of proactive marketing practices in enhancing the dimensions of leadership of banking institutions in general and the banks of the research sample (Trade Bank of Iraq), and the main objective of the research was to identify the impact of proactive marketing with its practices (product creativity, risk management, market recognition, focus on customers) and use them in order to enhance and apply the dimensions of leadership of the banking institution (pre-planning, efficiency, effectiveness). (Product creativity, risk management, market recognition, focus on customers) The dimensions of customer satisfaction were adopted as a dependent variable, and a number of the Iraqi Trade Bank operating in the Karbala governorate were selected to test this study through a questionnaire as an essential tool in collecting various data On the field side, it included (48) individual managers of banks, their departments and units, as well as personal interviews.